Symbol-Flipping Method for Block Decoding in Bit-Patterned Magnetic Recording - Siwakon Sokjabok; Mutita Mattayakan; Chanon Warisarn; Santi Koonkarnkhai; Piya Kovintavewat (My University, 2021)
Bit-patterned magnetic recording (BPMR) technology can provide an areal density (AD) up to 15 Terabit per square inch (Tb/in 2 ). However, the consequence of an increased AD results in severe inter-symbol interference (ISI) and inter-track interference (ITI). In practice, a run-length limited (RLL) code can be used to alleviate this problem. Therefore, this research proposes a symbol-flipping method in an iterative detection scheme between a soft-output Viterbi algorithm (SOVA) detector and an RLL decoder to help reduce errors resulting from these two interferences in a BPMR system. Simulation results reveal that the proposed system performs better than the same system architecture without the symbol-flipping method by 0.5 decibels at an AD of 5 Tb/in 2 .
Keywords: Cellular Automata and Applications; Magnetic properties of thin films; Advanced Data Storage Technologies